PREVALENCE AND INFLUENCERS OF INTESTINAL PROTOZOA INFECTION AMONG SCHOOL CHILDREN AT KIGEME REFUGEE CAMP: NYAMAGABE DISTRICT - RWANDA) - S. A. L, MUSHIMIYE; Joseph, BIZIMANA; Bosco, RUGAZU John; Ivan, GAHIMA; Francis, WABWIRE Paul (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Entamoeba histolytica and Giardia lamblia are two of the most significant andwidespread diarrhea-related parasitic protozoa in the world (N’Goran, 2010). Schoolgoing children are highly prone and affected by these protozoa causing gastro-entericdisorders (Farzana, et al., 2015). Personal hygiene, use of toilet, consumption of cleanand boiled water are very important eradication measure. Cross section study withpurpose of determining the prevalence of the disease involving 126 children between 6 –13 years was done in KIGEMA Refugee Camp. Data was collected using questioners andexamination of stool samples.Results revealed prevalence is 50(39.7%) among the population with 39(30.9%) havingE.histolityca, 6(4.7%), G.lamblia and 5(3.9%) having both. The prevalence was strongly associated with none-wash of hands before eating (X2=9.297, df=6, p=0.002), aftertoileting (X2=12.007, df=6, p=0.001), consumption of un boiled water (X2=16.177, df=6,p=0.001) and gender (p=0.003). Adequate health education regarding hygiene as well asboiling water before use are key issue in the fight against the disease in this camp.